Catalogação, formas de representação e construções mentais - Santos, Plácida Leopoldina Ventura Amorim da Costa [UNESP] (2013)
The cataloging process, is responsible for building systems consisting of sets of interconnected elements and combined forms of representation, creating tools to facilitate the flow of information in various informational environments. It presents structures that offer favorable conditions for access to formal codes of symbolic representation and to the channels of information transfer, performing with competence the decoding and encoding of codes and rules used to represent knowledge and to describe information, documents and resources. The objective of this paper is to present the challenge of transforming operational data into consistent information, the role of the forms of representation and the mental constructions for defining the memory markers of users of catalogs. It shows as results the memory markers indicated by three categories of users for the description of a book like resource and points to the need of collaborative and cooperative work in cataloging and to the need of catalog modelling focused on the user.